Carbon Monoxide Level Forecasting Using Neural Network. - Mamat, Mazlina; Mashor, Mohd. Yusof; Saad, Abdul Rahman; Sadullah, Ahmad Farhan (2002)
The neural network approach on forecasting Carbon Monoxide concentration is one topic of air quality research due to the health effects caused by Carbon Monoxide gasses in urban area.